New Horizons in Vision Science, Optometry and Ocular Surface - Sánchez-González, José-María; Rocha-de-Lossada, Carlos; Cerviño, Alejandro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aimed to explore the cutting-edge advancements in vision science, optometry, and ocular surface research. In an era marked by rapid technological progress, there is an imperative to understand how innovations in diagnostic tools, treatment protocols, and computational models are reshaping our understanding of ocular health and vision care. We invited contributions that delved into novel methodologies, uncovered new aspects of ocular physiology, or offered fresh perspectives on the management of eye conditions.